SWEPT-SOURCE OPTICAL COHERENCE TOMOGRAPHY DETECTION OF BRUCH MEMBRANE AND CHORIOCAPILLARIS ABNORMALITIES IN SORSBY MACULAR DYSTROPHY. Issue 9 (September 2022) - Iyer, Prashanth G.; Zhou, Hao; Zhang, Qinqin; Chu, Zhongdi; Shen, Mengxi; Shi, Yingying; Liu, Jeremy; Trivizki, Omer; Lam, Byron L.; Wang, Ruikang K.; Gregori, Giovanni; Rosenfeld, Philip J.
Abstract : Swept-source optical coherence tomography angiography imaging of undiagnosed relatives in a family with Sorsby macular dystrophy detected reticular pseudodrusen and abnormalities in Bruch membrane thickness, choriocapillaris thickness, and choriocapillaris perfusion only in family members shown to carry the Sorsby macular dystrophy mutation. Abstract : Purpose: Swept-source optical coherence tomography angiography (SS-OCTA) was used to analyze Bruch membrane (BM) and choriocapillaris (CC) abnormalities in undiagnosed family members with Sorsby macular dystrophy (SMD). Methods: In a family with SMD ( TIMP3 Tyr191Cys), SS-OCTA imaging was performed using the 6 × 6 mm scan patter and previously validated algorithms to detect abnormalities in BM and the CC, as well as the presence of reticular pseudodrusen and macular neovascularization. Genetic analyses were performed for TIMP3 mutations. Results: Of eight family members, two were previously diagnosed with SMD and six were asymptomatic. SS-OCTA imaging of the 33-year-old proband revealed type 1 macular neovascularization in the left eye and bilateral reticular pseudodrusen, thickening of BM, CC thinning, and increases in CC flow deficits. A TIMP3 mutation was confirmed. His niece, despite having no clinical evidence of SMD, showed BM thickening and CC thinning on SS-OCTA. A TIMP3 mutation was confirmed. The proband's younger nephew and niece also carried the TIMP3 mutation without clinical evidence of SMD. Two additional members had normal examinations, unremarkable SS-OCTA findings, and no TIMP3 mutation. Conclusion: Swept-source optical coherence tomography angiography imaging can detect BM and CC abnormalities in vivo in subjects unaware of their TIMP3 status in a family with SMD.